Internalisasi Nilai Pancasila melalui Pendidikan Kewarganegaraan: Pembentukan Kepemimpinan Siswa SMA N 1 Siantar - Anita Sitanggang; Elisabet Sesilia Purba; Ariel Jonivedi Silalahi; Bella Sonia Sianturi; Kasihta Santana Saragih (Yayasan Bayt Shufiya Nusantara, 2026)
This research examines the process of internalizing Pancasila values through Civics Education (PKn) as an instrument for cultivating students' leadership habitus at SMA Negeri 1 Siantar. The primary focus of this study is to explore how ideological values are transformed into daily behavior through pedagogical structures and school policies. Employing a descriptive-analytical qualitative approach, data were gathered through participatory observation, in-depth interviews with the principal, teachers, and students, as well as documentation studies. Data analysis was conducted circularly to capture the underlying meanings within instructional and organizational practices. The research findings indicate that the internalization of Pancasila values at this school transcends mere cognitive transmission; rather, it is achieved through the implementation of deep learning strategies in Civics Education, which are integrated into the practical actions of the Kurikulum Merdeka (Independent Curriculum). This process is reinforced by the principal's transformative leadership, which creates an ecosystem of value discipline through routine flag ceremonies and extracurricular activities (Paskibra, Scouts, Rohis, and KSK). These activities are proven to construct norms of mutual cooperation (gotong royong) and tolerance as a collective identity for the students. This study concludes that the formation of a Pancasila-based leadership habitus is highly dependent on the consistency between exemplary school leadership and the availability of spaces for students' self-actualization in negotiating diversity.